The ratio of length at first maturity to maximum length across marine and freshwater fishes. Issue 2 (6th January 2022) - Chen, Zhaomin; Bigman, Jennifer; Xian, Weiwei; Liang, Cui; Chu, Elaine; Pauly, Daniel
Abstract: The prevailing determinant of maturation in fishes is thought to be a redirection of energy from growth to reproduction. Instead, the Gill Oxygen Limitation Theory predicts that maturation, and thus reproduction, is induced when a fish reaches a critical ratio of oxygen supply to demand ( Q m /Q maint ). The consistency of this critical ratio has been previously documented in many fishes, but a broader test was lacking. In this study, the authors assess if this critical ratio is consistent across 132 unique fish species, as measured by the slope of the relationship between L max D and L m D, where L max is the maximum length reached in a given population, L m is the mean size at first maturity in that population and D is a gill‐related exponent which renders the L max D /L m D ratio equivalent to the Q m /Q maint ratio. The authors found that across all species, the L max D /L m D ratio was 1.40 (95% c.i. 1.38–1.42), which was not significantly different from that previously estimated across other species groups (1.35, 95% c.i. 1.22–1.53), especially when phylogenetic relationships were considered (1.25, 95% Bayesian credible interval 1.09–1.40). The consistency of the L max D /L m D ratio across taxa, which expresses the difference in metabolic rate at maturity and maximum size, suggests that the scaling of gill surface area is the factor that underlies this ratio, and which triggers the maturation in fishes.